Rheumatoid meningitis in the absence of rheumatoid arthritis: 2 cases - Juan Yang; Lu Liu; Jiahui Peng; Boya Ma; Xiao Yang (BMC Neurology, 2024)
Abstract Rheumatoid meningitis (RM) is a rare extra-articular manifestation of rheumatoid arthritis (RA) that has been increasingly recognized by neurologists. However, the diversity of its clinical manifestations makes its diagnosis difficult. RM does not have a unified diagnostic standard, and its link with RA needs to be studied further. Here we report two cases of RM without a history of RA. The first patient, an 80-year-old woman, presented with sudden unilateral limb weakness, with brain MR showing abnormal signals in the leptomeningeal of the right frontal parietal. Subarachnoid hemorrhage was excluded after imaging examination, and infectious meningitis was ruled out after cerebrospinal fluid (CSF) examination. The patient was diagnosed as having RM, she had increased levels of CCP and AKA, the markers of RA, but no history of the disease or other clinical manifestations of it. Another case, a 65-year-old man, was hospitalized with Bell’s palsy. We found that he had intracranial imaging changes highly consistent with those characteristic of RM during his routine examination. Except for the left peripheral facial palsy, the patient had no other neurological signs or symptoms and no RA history. After a careful physical examination, we found no joint or other manifestations or serological abnormalities consistent with RA (RF, CCP, AKA, etc.). However, after excluding infection meningitis and considering the patient’s unique imaging results, we diagnosed him as having RM. We report these two cases as references for clinical diagnosis and treatment of RM, providing a discussion of our rationale.